UMPSA receives a courtesy visit from the Director of Civil Defence Force (APM) Pahang State - Mohd Raizalhilmy, Mohd Rais (UMPSA, 2023)
PEKAN, 10 October 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received a courtesy visit from the Director of the Pahang State Civil Defence Force (APM), Colonel (PA) Che Adam Abd. Rahman, to the Commander of the Civil Defence Student Unit (Kor Sispa), Honorary Civil Defence, Professor Ts. Dr. Kamal Zuhairi Zamli, who is also the Deputy Vice-Chancellor (Research and Innovation) of UMPSA.